Epidemiology of Macular Edema in Uveitis. (17th February 2019) - Accorinti, Massimo; Okada, Annabelle A.; Smith, Justine R.; Gilardi, Marta
ABSTRACT: Purpose: To describe the epidemiology of macular edema (ME) in patients with uveitis. Methods: Review of articles listed on PubMed pertaining to uveitic ME. Results: Reported rates of uveitic ME ranging from 20% to 70%, depending on the ancillary tests used (fundus examination, fluorescein angiography, optical coherence tomography). Macular edema might develop due to uveitis itself, or occur as an adverse effect of drugs taken for different diseases. It is more frequently observed in adults than in children, in chronic uveitis, and in intermediate uveitis. Males with ankylosing spondylitis are more prone to develop ME than females. Three patterns of uveitic ME are observed, either isolated or in combination: cystoid ME, the most frequently encountered pattern seen in up to 80% of cases, diffuse ME and serous retinal detachment. Conclusion: Older age, chronicity of uveitis and intermediate uveitis are risk factors for the development of ME in patients with uveitis.